2021
DOI: 10.2147/jhc.s322289
|View full text |Cite
|
Sign up to set email alerts
|

Current Landscape and Future Directions of Biomarkers for Immunotherapy in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the most common liver cancer and one of the leading causes of cancer-related deaths in the world. Multiple immunotherapeutic approaches have been investigated to date, and immunotherapy has become the new standard of care therapy in HCC. However, the current role of immunotherapy in HCC remains non-curative. Given this context, a high priority for oncology is understanding the biomarkers that predict clinical response to immunotherapy, have the potential to improve patient sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…In the CheckMate 040 trial, tumor responses were also independent of PDL1 status [ 93 ]. Other cellular factors and immune signatures that could serve as biomarkers to predict ICI immunotherapy outcomes were summarized previously [ 94 ].…”
Section: Challenges and Opportunities In Ici Therapy For Hccmentioning
confidence: 99%
“…In the CheckMate 040 trial, tumor responses were also independent of PDL1 status [ 93 ]. Other cellular factors and immune signatures that could serve as biomarkers to predict ICI immunotherapy outcomes were summarized previously [ 94 ].…”
Section: Challenges and Opportunities In Ici Therapy For Hccmentioning
confidence: 99%
“…These questions are of particular importance for several reasons. First, immunotherapy is a developing HCC treatment 15 and the ability to combine locoregional therapies and immunotherapy is of great interest with early studies demonstrating reason to be hopeful. 16 , 17 TARE is of particular interest as preclinical studies of external beam radiation have suggested that higher doses of radiation to the tumor increase the likelihood of inducing a positive immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the promising prognostic results of immunotherapy for most patients with advanced HCC, one third of patients with advanced HCC did not benefit from immunotherapy, and up to one fourth developed high-grade immune-related adverse events [ 10 ]. Thus, not all patients benefit equally.…”
Section: Introductionmentioning
confidence: 99%
“…To date, we lack biomarkers that can predict the response to immunotherapy, and thus, provide guidance in clinical decisionmaking. To facilitate decision-making, novel biomarkers are needed, particularly as the treatment with those new agents distinctly differs from the treatment with tyrosine kinase inhibitors [9,10]. Apart from tumor cell-derived and tumor microenvironment-derived biomarkers, in advanced HCC stages, specific laboratory parameters, like alpha-fetoprotein (AFP), and its changes during treatment, and inflammatory parameters, like C-reactive protein, have shown strong correlations with patient prognosis [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation